Calcaneus length determines running economy: Implications for endurance running performance in modern humans and Neanderthals - Raichlen, D. A.; Armstrong, H.; Lieberman, D. E. (Journal of Human Evolution, 2011)
The endurance running (ER) hypothesis suggests that distance running played an important role in the evolution of the genus Homo. Most researchers have focused on ER performance in modern humans, or on reconstructing ER performance in Homo erectus, however, few studies have examined ER capabilities in other members of the genus Homo. Here, we examine skeletal correlates of ER performance in modern humans in order to evaluate the energetics of running in Neandertals and early Homo sapiens. Recent research suggests that running economy (the energy cost of running at a given speed) is strongly related to the length of the Achilles tendon moment arm. Shorter moment arms allow for greater storage and release of elastic strain energy, reducing energy costs. Here, we show that a skeletal correlate of Achilles tendon moment arm length, the length of the calcaneal tuber, does not correlate with walking economy, but correlates significantly with running economy and explains a high proportion of the variance (80%) in cost between individuals. Neandertals had relatively longer calcaneal tubers than modern humans, which would have increased their energy costs of running. Calcaneal tuber lengths in early H. sapiens do not significantly differ from those of extant modern humans, suggesting Neandertal ER economy was reduced relative to contemporaneous anatomically modern humans. Endurance running is generally thought to be beneficial for gaining access to meat in hot environments, where hominins could have used pursuit hunting to run prey taxa into hyperthermia. We hypothesize that ER performance may have been reduced in Neandertals because they lived in cold climates.